่Ecotourism Mix, Good Practice, and Green Marketing: An Approach Towards the Quality Tourism Business - Sangpikul, Aswin (Journal of Community Development Research (Humanities and Social Sciences), 2017)
During the past decades, the literature on tourism marketing contributes the knowledge to large businesses in the tourism industry (e.g. hotels, airlines, restaurants). However, the knowledge on green marketing given to a small business like the tour operators in reducing tourism impacts is limited. In addition, the global trend concerns more on the environmental issues. In particular, there are needs for promoting responsible tourism businesses, ethical conducts and green marketing. This article, therefore, has the objectives to 1) introduce the ecotourism mix contributing to the identification of ecotourism good practice for the tour operators and 2) provide green marketing implications that care the environment. Responsible tour operators and ecotourism tour operators may implement the suggested green marketing to develop or improve their tour conducts in order to be the quality tourism business and the alternatives for travelers.
Keywords: Ecotourism (Niche Tourism/Non Consumptive Tourism), Ecotourism Mix, Good Practice, Green Marketing, Environmental Friendly Product, Tour Operator